A phase-shifterless beam scanning array antenna for agricultural applications - Ngamjanyaporn, Phaisan; Krairiksh, Monai (My University, 2017)
This paper presents a phase-shifterless beam scanning array antenna that three elements of circular array are pattern reconfigurable Yagi-Uda antennas. To minimize the antenna complexity, instead of using four beams of each element, one element uses fixed beam while the other two elements can switch radiation pattern in two directions. The radiation characteristics of the array are simulated using 4NEC2 simulator to find out the suitable array parameters. The suitable element orientation of 45° and the array radius of 0.65λ, and with non-uniform amplitude excitation, the array provides four beams that cover 150° with gain 7-9 dBi. The array has been validated by experiments. The four beams of the array show good agreement with the simulated ones.
Keywords: Beam-scanning antenna; Phase-shifterless array antenna; Yagi-Uda antenna